2008
DOI: 10.1021/jf801297w
|View full text |Cite
|
Sign up to set email alerts
|

Survey of the trans-Resveratrol and trans-Piceid Content of Cocoa-Containing and Chocolate Products

Abstract: Dietary resveratrol (3,4',5-trihydroxystilbene) has been implicated in the health benefits associated with grapes and red wine, more specifically with potential benefits for metabolic syndrome, energy use, and increased endurance. Levels of trans-resveratrol and its glucoside, trans-piceid, were determined in 19 top selling commercially available cocoa-containing and chocolate products from the U.S. market. Amounts of trans-resveratrol and trans-piceid were closely correlated with the amount of nonfat cocoa so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
1
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(79 citation statements)
references
References 28 publications
0
73
1
5
Order By: Relevance
“…Dark chocolate, a food that contains large quantities of phenolic compounds, is reportedly a good source of antioxidants (Lee, Kim. Lee, & Lee, 2003;Hurst, Glinski, Miller, Apgar, Davey, & Stuart, 2008;Niemenak, Rohsius, Elwers, Ndoumou, & Lieberei, 2008). Since almonds are also a rich source of vitamin E, an antioxidant, several manufacturers have dark chocolate products on the market that incorporate almonds and berries (e.g.…”
Section: Effect Of Ph On Amandin Recoverymentioning
confidence: 99%
“…Dark chocolate, a food that contains large quantities of phenolic compounds, is reportedly a good source of antioxidants (Lee, Kim. Lee, & Lee, 2003;Hurst, Glinski, Miller, Apgar, Davey, & Stuart, 2008;Niemenak, Rohsius, Elwers, Ndoumou, & Lieberei, 2008). Since almonds are also a rich source of vitamin E, an antioxidant, several manufacturers have dark chocolate products on the market that incorporate almonds and berries (e.g.…”
Section: Effect Of Ph On Amandin Recoverymentioning
confidence: 99%
“…Therefore, both trans-stilbenes were measured just by selecting m/z 229. As in hop, grape juices, wine, and cocoa-containing products (23,27,34,35), trans-piceid emerged as the major form ( Figure 1A; its lower recovery is balanced on the chromatogram by the two times higher sensitivity of the mass spectrometer for piceid than for its aglycon). Only three cocoa liquors (Peru 06, Madagascar 06, and New Guinea 06) exhibited a distinct profile with a higher peak for transresveratrol ( Figure 1B).…”
Section: Resultsmentioning
confidence: 94%
“…In cocoa liquor, 0.5 mg/kg of trans-resveratrol and up to 1.2 mg/kg of its glucoside trans-piceid have been determined (12). More recently, Hurst et al (27) reported much higher levels in some cocoa-derived products: from 0.09 to 1.85 mg/kg and from 0.35 to 7.14 mg/kg for trans-resveratrol and trans-piceid, respectively. Their highest values were obtained for cocoa powder.…”
Section: Introductionmentioning
confidence: 99%
“…29 Red grapes and red wines earn star status for their high levels of resveratrol, with Spanish grapes taking the top prize, providing as much as 1,890 micrograms in a 5-ounce glass. 30,31 Grapes only have resveratrol in the skins and the amount varies according to the type of grape and whether the plant is exposed to fungal infection, a form of stress that the plant responds to by producing resveratrol to fend off infection.…”
Section: In Foodsmentioning
confidence: 99%